If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = -1y + -1t Reorder the terms: 3x = -1t + -1y Solving 3x = -1t + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = -0.3333333333t + -0.3333333333y Simplifying x = -0.3333333333t + -0.3333333333y
| 90+5f+2+122=180 | | 6(n+7)=7n-4 | | 4x^2-15x=-3x^2-2x-6 | | 8x+22y=10 | | 3-9(4x+12)=6(4x+24-12) | | 3-9(4x+12)=6(4x+24-12) | | y=6.3333+3x | | 6m+-3=-15+2m | | 3.75b+50.00=800 | | 2(w-5)-8w=26 | | 2/3m=m-2/9 | | 6*11+8= | | -5x+2(3x+6)=0 | | x=3/y | | 3.75b+50.00=400 | | -3(4a+3)+4(6x+1)=43 | | 90+5f+2=122 | | 4x=-10x-112 | | 3/(X-6)=6 | | 3y=-19+9x | | 1x+300=1.50x+200 | | 1x+300=1.50x+200 | | 90/0.60 | | Y=8x+.20 | | 10x-25xy= | | 5t/4=20 | | y=-2xsquare+3 | | p^3-w^12=0 | | 122+5f+2=90 | | 18x^2-13x+3=0 | | x^(7/11)=14 | | 16a-4(5a-7)=4 |